Underlying Factors of the Use of E-Commerce by SMEs in Tanjung Lesung - Rofian Almas Akbar; Adhi Setyo Santoso; Andi Ina Yustina; Hajanirina Andrianantenaina (AIBPM Publisher, 2022)
This study aims to analyze the factors that the SME onwers in Tanjung Lesung need to promote their products through e-commerce. This study employed a quantitative method, presenting 23 questions anticipated to provide insight into the research problem. This study purposively selected 300 samples of small and medium-sized business owners who use the internet to sell their products. The results show that the management relationship between productivity and actual behavior revealed a favorable relationship between perceived usefulness and actual behavior, but a negative relationship between external pressure on actual behavior and organizational support for actual behavior. The study's limitations included the impact of internet usage via e-commerce on small and medium-sized businesses. Keywords: Actual Behavior, External Pressure, Managerial Productivity, Organizational Support, Perceived Usefulness